National Committee on Atomic Information records - National Committee on Atomic Information
Correspondence with scientists and organizations, memoranda, speeches, reports, articles, financial records, clippings, printed matter, photographs, and other papers reflecting the committee's attempts to promote understanding of the implications of atomic energy in a nontechnical, easily understood form through the presentation of a popular program in the press, on the radio, and with a speaker's bureau. Organizations represented include the American Federation of Labor, Congress of Industrial Organizations (U.S.), Federal Council of the Churches of Christ in America, League of Women Voters (U.S.), and National Council of Jewish Women.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Established in 1945 as a clearinghouse for information on the atomic age. Dissolved in 1948.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American Federation of Labor; Congress of Industrial Organizations (U.S.); Federal Council of the Churches of Christ in America; League of Women Voters (U.S.); National Council of Jewish Women; Nuclear energy -- Popular works; Nuclear energy -- Societies, etc